Semantic Features Of Names Of Ceremonial Clothes In Uzbek And English Languages (Open Academia: Journal of Scholarly Research, 2026)
This article investigates the semantic characteristics of ceremonial and formal costume names in Uzbek and English. Clothing terminology in both languages reflects not only denotative meanings related to garments but also complex cultural, symbolic, social, and ritual functions. Through a comparative semantic and linguocultural approach, the study analyzes how ceremonial dress names encode national identity, social hierarchy, religious values, gender roles, and historical traditions. The findings demonstrate that Uzbek ceremonial costume lexicon tends to preserve stronger ritual-sacral and ethnocultural components, while English formal costume terminology is often institutional, functional, and status-oriented